Digital Marketing Sebagai Strategi Pengembangan dan Inovasi Produk Kopi Bikla di Desa Bangsalsari Kabupaten Jember - Asyrofi Asyrofi; Agus Supriono; Cindera Rosa Damascena; Julian Adam Ridjal; Ebban Bagus Kuntadi; M. Rondhi; Ahmad Zainuddin (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a significant contribution to national economic growth and the smooth distribution of goods and services. However, market competition and national economic dynamics pose serious challenges to the sustainability of MSMEs, especially in terms of competitiveness and technological adaptation. The development of digitalization opens up great opportunities for MSMEs to increase production efficiency and expand marketing reach through online sales platforms. Unfortunately, the limited knowledge and skills of MSME actors in managing digital marketing strategies leads to low optimization of this potential. This research aims to examine the needs of MSME assistance in Bangsalsari Village, Jember Regency, in order to increase business capacity and digital marketing effectiveness. The method used is a qualitative approach through field observation and interviews with MSME actors. The results of the study show that structured and sustainable mentoring can increase business actors' understanding of digital strategies, expand market access, and encourage the creation of new jobs. Thus, technology-based assistance programs and local needs are strategic solutions in strengthening the resilience and competitiveness of MSMEs in the midst of national economic challenges.